Pengaruh Pembiayaan Syariah Terhadap Kinerja Keuangan Perbankan Syariah - Siti Masitoh; Rachma Zannati (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
This study aims to analyze Islamic financing; Mudharabah, Murabahah, Financing To Deposit Ratio, Non Performing Financing on the financial performance of Islamic Banking in Indonesia. Based on the sampling criteria, there are 15 Islamic Banks, namely a combination of Islamic Commercial Banks and Sharia Business Units with a research period of 5 years (2014-2018). The research analysis used is panel data regression analysis using E-Views 10. Based on the results of data analysis, only Non-Performing Financing has a significant effect on Return on Assets. Meanwhile, Mudharabah, Murabahah, and Financing to Deposit Ratio have no significant effect on Return On Assets. The research implication is that not all Islamic financing can contribute to the financial performance of Islamic banking. Keywords: Mudharabah, Murabahah, Financing to Deposit Ratio, Non Performing Financing and Profitability.